Coupling the immunomodulatory properties of the HDAC6 inhibitor ACY241 with Oxaliplatin promotes robust anti-tumor response in non-small cell lung cancer. (31st December 2022) - Bag, Arup; Schultz, Andrew; Bhimani, Saloni; Stringfield, Olya; Dominguez, William; Mo, Qianxing; Cen, Ling; Adeegbe, Dennis
ABSTRACT: While HDAC inhibitors have shown promise in hematologic cancers, their efficacy remains limited in solid cancers. In the present study, we evaluated the immunomodulatory properties of the HDAC6 inhibitor, Citarinostat (ACY241) on lung tumor immune compartment and its therapeutic potential in combination with Oxaliplatin. As a single agent, ACY241 treatment promoted increased infiltration, activation, proliferation, and effector function of T cells in the tumors of lung adenocarcinoma-bearing mice. Furthermore, tumor-associated macrophages exhibited downregulated expression of inhibitory ligands in favor of increased MHC and co-stimulatory molecules in addition to higher expression of CCL4 that favored increased T cell numbers in the tumors. RNA-sequencing of tumor-associated T cells and macrophages after ACY241 treatment revealed significant genomic changes that is consistent with improved T cell viability, reduced inhibitory molecular signature, and enhancement of macrophage capacity for improved T cell priming. Finally, coupling these ACY241-mediated effects with the chemotherapy drug Oxaliplatin led to significantly enhanced tumor-associated T cell effector functionality in lung cancer-bearing mice and in patient-derived tumors. Collectively, our studies highlight the molecular underpinnings of the expansive immunomodulatory activity of ACY241 and supports its suitability as a partner agent in combination with rationally selected chemotherapy agents for therapeutic intervention in NSCLC.